Transformasi Kepemimpinan dalam Era Digital: Mengintegrasikan Teknologi dan Praktik Keberlanjutan - Ahmad Abadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
In the increasingly digital era, leadership transformation has become a key factor in achieving organizational sustainability. This study aims to explore how leaders can integrate technology with sustainability practices to create long-term value. The methodology used in this study includes a literature review, surveys, in-depth interviews, and case study analysis of companies that have successfully implemented technology and sustainability integration strategies. The results indicate that adaptive and visionary leadership is crucial for implementing technological innovations that support sustainability. Furthermore, the main challenges faced by leaders are resistance to change and a lack of resources for investment in new technologies. This study is expected to provide guidance for leaders in facing challenges and capitalizing on opportunities in the digital era to achieve sustainability goals.